The Influence of Blackpink as Tokopedia’s Brand Ambassador on Student Online Purchase Decision at Tokopedia E-Marketplace Period 2022 - Keythline Priscilla Putri Maharani; Panji Nandiasa Ananda Mukadis; Ruth Nattassha (Digismantech (Jurnal Program Studi Bisnis Digital), 2023)
Korean Wave phenomena in Indonesia can be seen by its demand among the millennials, especially when it comes to Korean pop music or simply called K-pop. One research has concluded that BTS and Blackpink (very popular music groups in South Korea has proven to significantly influence purchase decisions among Tokopedia buyers. However, there have been no research focusing on university students as research subject. Based on our analysis from the data gathered from 100 respondents concluded that there is positive influence by Blackpink as Tokopedia brand ambassador to the purchase decision on Tokopedia for 2022 year periode. This conclusion has been proven by the structured validity and reliability test, including normality, regression, and hypothesis. Hence, Tokopedia can continue to use brand ambassador and always try to find the best possibility of the possible ambassadors and how to activate them.